The identification of beneficial owners through the application of the doctrine of piercing the corporate veil by judges - Zulmawan, Wawan; Khaliza, Ashila Raisya; Suhendra, Christabel Daniella; Pongsirinding, Fisa Ande’; Inly, Naomi; Dante, Russell; Pendang, Serlita Ruben (Priviet Social Sciences Journal, 2026)
Corporate crime, such as corruption, is currently on the rise, one example being the practice of concealing identities through the pretext of beneficial ownership and nominee agreements. This issue requires law enforcement to focus not only on the formal corporate structure but also on tracing the parties who actually control and benefit from the corporation. This study aims to analyze the legal status of nominee agreements and the importance of beneficial ownership transparency in closing loopholes in corporate law in Indonesia. It also analyzes the application of the "piercing the corporate veil" doctrine in Supreme Court Decision Number 4950 K/Pid.Sus/2023. The method used in this research is normative juridical, using statutory, conceptual, and case study approaches. This study explains that although regulations regarding beneficial ownership exist, their implementation is still not fully implemented, primarily due to low awareness of reporting compliance and the continued prevalence of nominee practices. Based on existing decisions, the Supreme Court outlines a more progressive approach by applying the "piercing the corporate veil" doctrine to hold beneficial owners criminally liable, even if they are not listed in the company structure. This shifts from a normative approach to the application of substantive law. Therefore, there is a need for strengthening regulations, increasing oversight, and ensuring data integrity between institutions so that transparency and accountability of beneficial owners can truly be realized and are no longer exploited as loopholes for corruption. Keywords: beneficial owner, corporate corruption, criminal liability, nominee agreement, piercing the corporate veil.